Wedelolactone Attenuates Pulmonary Fibrosis Partly Through Activating AMPK and Regulating Raf-MAPKs Signaling Pathway - Yang, Jin-yu; Tao, Li-jun; Liu, Bei; You, Xin-yi; Zhang, Chao-feng; Xie, Hai-feng; Li, Ren-shi (Frontiers in Pharmacology, 2019)
Pulmonary fibrosis is common in a variety of inflammatory lung diseases, there is currently no Pulmonary fibrosis is common in a variety of inflammatory lung diseases, there is currently no effective clinical drug treatment. It has been reported that the ethanol extract of Eclipta prostrata L. can improve the lung collagen deposition and fibrosis pathology induced by bleomycin (BLM) in mice. In the present study, we studied whether wedelolactone (WEL), a major coumarin ingredient of E. prostrata, provided protection against BLM-induced pulmonary fibrosis. ICR or C57/BL6 strain mice were treated with BLM to establish lung fibrosis model. WEL (2 or 10 mg/kg) was given daily via intragastric administration for two weeks starting at 7 day after intratracheal instillation. WEL at 10 mg/kg significantly reduced BLM-induced inflammatory cells infiltration, pro-inflammatory factors expression, and collagen deposition in lung tissues. Additionally, treatment with WEL also impaired BLM-induced increases in fibrotic marker expression (collagen I and -SMA) and decrease in an anti-fibrotic marker (E-cadherin). Treatment with WEL significantly prevented BLM-induced increase in TGF-1 and Smad2/3 phosphorylation in the lungs. WEL administration (10mg/kg) also significantly promoted AMPK activation compared to model group in BLM-treated mice. Further investigation indicated that activation of AMPK by WEL can suppressed the transdifferentiation of primary lung fibroblasts and the epithelial mesenchymal transition (EMT) of alveolar epithelial cells, the inhibitive effects of WEL was significantly blocked by an AMPK inhibitor (compound C) in vitro. Together, these results suggest that activation of AMPK by WEL followed by reduction in TGF1/Raf-MAPK signaling pathways may have a therapeutic potential in pulmonary fibrosis.